THE EFFECT OF PLAYING SNAKE AND LADDER TOWARD THE RESULT STUDY OF ARITHMETIC ADDITION FOR STUDENT WITH MENTALLY RETARDED STUDENT - Sari, Arianti Iman; Wahyuno, Endro (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
The purpose of this research were to describe: (1) the study result of arithmetic addition operation for fourth grade student with mentally retarded in SDLB before playing the Snake and Ladder activity (2) the study result of arithmetic addition operation for fourth grade student with mentally retarded in SDLB after playing the Snake and Ladder activity (3) the effect of Snake and Ladder playing toward the result study of arithmetic addition for fourth grade student with mentally retarded SDLB. This research used SSR (Single Subject Research) with A-B-A design. Collecting the data was done by using assessment instrument, tests and observations. The result of this research showed that playing Snake and Ladder affected the studyÂ result of arithmetic addition operation for fourth-grade children with mentally retarded student in SDLB.Tujuan penelitian ini adalah mendeskripsikan (1) Hasil belajar penjumlahan siswa kelas 4 SDLB sebelum melakukan kegiatan bermain Ular Tangga (2) Hasil belajar penjumlahan siswa kelas 4 SDLB sesudah melakukan kegiatan bermain Ular Tangga (3) Pengaruh bermain Ular Tangga terhadap hasil belajar penjumlahan siswa kelas 4 SDLB. Penelitian ini menggunakan rancangan penelitian SSR (Single Subject Research) dengan desain A-B-A. Pengumpulan data menggunakan instrumen assesmen, tes dan observasi. Hasil penelitian menunjukkan bermain ular tangga berpengaruh terhadap hasil belajar penjumlahan siswa tunagrahita kelas 4 SDLB.